Biochemical, Thrombolytic and Pharmacokinetic Properties of rt-PA P47G, K49N, a Substitution Variant of Human Tissue-Type Plasminogen Activator - Nelles, L; Li, X-K; Vanlinthout, I; De Cock, F; Lijnen, H R; Collen, D (Thrombosis and Haemostasis, 1992)
rt-PA P47G, K49N, a substitution variant of recombinant human tissue-type plasminogen activator (rt-PA), in which proline at position 47 and lysine at position 49 were replaced by glycine and asparagine respectively, was previously described by Ahem et al. (J Biol Chem 1990; 265: 5540—5) to have an extended in vivo half-life with unaltered in vitro fibrinolytic properties. Because this variant might possess an increased in vivo thrombolytic potency, we have constructed its cDNA, expressed it in Chinese hamster ovary cells and determined its biochemical, thrombolytic and pharmacokinetic properties relative to those of home-made rt-PA and of alteplase (Actilyse®).The specific fibrinolytic activities on fibrin plates were 160,000 ± 17,000, 210,000 ± 88,000 and 460,000 ± 72,000 IU/mg (mean ± SEM) for rt-PA P47G, K49N, rt-PA and alteplase, respectively, while the catalytic efficiencies for plasminogen activation (k2Km) in the absence of fibrin were comparable (1.1 to 1.7 × 10-3 μM-1s-1). Fibrin enhanced the rate of plasminogen activation by rt-PA P47G, K49N 100-fold and by both wild-type molecules 390-fold. Binding of the variant rt-PA to fibrin was significantly reduced, but its affinity for lysine-Sepharose was unaltered. In an in vitro clot lysis system, consisting of a radiolabeled human plasma clot submersed in plasma, 50% clot lysis in 2 h required 0.67 ± 0.14 pg/ml rt-PA P47G, K49N, 0.36 ± 0.01 pg/ml rt-PA and 0.17 ± 0.01 pg/ml alteplase, respectively (mean ± SEM; n = 3 or 4). At these doses residual fibrinogen levels at 2 h were in excess of 80%.The thrombolytic properties were examined in a hamster pulmonary embolism model. The thrombolytic potency, expressed as percent lysis per mg activator administered per kg body weight, was 160 ± 28 for rt-PA P47G, K49N, 150 ± 36 for wild-type rt-PA and 310 ± 42 for alteplase. The specific thrombolytic activity, expressed as percent lysis per pg steady-state t-PA-related antigen level per ml plasma, was 49 ± 18% for rt-PA P47G, K49N, 160 ± 49 for rt-PA and 500 ± 79 for alteplase. The clearance rates following bolus injection in hamsters were 0.18 ± 0.02, 1.9 ± 0.2 and 2.1 ± 0.1 ml/min respectively.Thus, the substitution of only two residues in wild-type rt-PA markedly reduces its clearance, but it also significantly alters its specific thrombolytic activity, resulting in a virtually unaltered thrombolytic potency.